Exploration of the Value and Meaning of Local Wisdom in the Fairy Tale "Mentiko Batuah" - Siti Ara; Selvi Alqorona; Aulia Rizki Hanifah; Ocha Nazira (International Journal of Multilingual Education and Applied Linguistics, 2025)
Fairy tales are an important part of oral literature that reflects the cultural values and local wisdom of the community that supports them. This study aims to explore the values and meanings of local wisdom in the fairy tale "Mentiko Batuah" , a folk tale from Aceh that is rich in moral messages and cultural symbolism. The research method used is descriptive qualitative with a hermeneutic approach and content analysis. Data were collected through literature and documentation studies, then analyzed to reveal the cultural messages contained in the narrative structure, characters, conflicts, and symbols in the story. The results of the study show that "Mentiko Batuah" contains various local wisdom values, such as honesty, responsibility, justice, and criticism of greed and betrayal. This story also functions as a medium for character formation and strengthening the cultural identity of the Acehnese people. Thus, this fairy tale not only acts as a means of entertainment, but also as an educational instrument that has relevance in the context of cultural and moral learning. This research is expected to be a contribution to the preservation of oral literature and the development of local cultural literacy studies in Indonesia.